2007
DOI: 10.1291/hypres.30.503
|View full text |Cite
|
Sign up to set email alerts
|

High Plasma Norepinephrine Levels Associated with .BETA.2-Adrenoceptor Polymorphisms Predict Future Renal Damage in Nonobese Normotensive Individuals

Abstract: Renal injury is common in obesity and hypertension. In the present study, we examined relationships between renal function alterations, plasma norepinephrine (NE), and 2-adrenoceptor polymorphisms in a longitudinal design over 5 years. In 219 nonobese, normotensive men with entry-normal renal function, we measured serum blood urea nitrogen (BUN), creatinine, creatinine clearance, plasma NE, homeostasis model assessment of insulin resistance (HOMA-IR), body mass index (BMI), total body fat mass, and blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 35 publications
(31 reference statements)
2
28
0
Order By: Relevance
“…7,[20][21][22] Zoccali et al 20,22 reported that the degree of sympathetic nervous activation might relate to the occurrence of fatal cardiovascular events. We also observed previously that 23 higher plasma NE levels could predict future renal injury in non-obese, normotensive individuals. Thus, one could speculate that sympathetic nervous activation might be the trigger linking obesity to impairment in renal function.…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations
“…7,[20][21][22] Zoccali et al 20,22 reported that the degree of sympathetic nervous activation might relate to the occurrence of fatal cardiovascular events. We also observed previously that 23 higher plasma NE levels could predict future renal injury in non-obese, normotensive individuals. Thus, one could speculate that sympathetic nervous activation might be the trigger linking obesity to impairment in renal function.…”
Section: Introductionsupporting
confidence: 81%
“…11,16,20 Our earlier study showed that high plasma NE levels could predict future renal injury even in non-obese, normotensive subjects. 23 In addition, we reported in a recent study that WL might contribute to the improvement in renal function that accompanies suppression of muscle sympathetic nerve activity in obese subjects with metabolic syndrome. 30 In the present study, we observed that long-term WL, even mild or moderate, was associated with a reduction in sympathetic activity with concomitant improvement in renal function, as assessed from measures of serum creatinine and estimated CCr.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…It is widely recognized that insulin resistance or hyperinsulinemia and sympathetic nervous activation relates to obesity and hypertension, 1-5 and these are known to be independent risk factors for future cardiovascular events. [6][7][8][9] Weight loss is an important preventative measure and is associated with a reduction in all-cause mortality. 10 Weight loss associated with lifestyle modifications such as diet and regular exercise are important and remain the first-line treatment for obesity and obesity-related hypertension.…”
Section: Introductionmentioning
confidence: 99%